SHBG, Sex Steroids, and Kyphosis in Older Men: The MrOS Study. (3rd November 2016) - Woods, Gina N; Huang, Mei‐Hua; Cawthon, Peggy M; Laughlin, Gail A; Schousboe, John T; McDaniels‐Davidson, Corinne; Cauley, Jane A; Orwoll, Eric; Barrett‐Connor, Elizabeth; Kado, Deborah M; ,
ABSTRACT: Accentuated kyphosis is associated with adverse health outcomes, including falls and fractures. Low bone density is a risk factor for hyperkyphosis, and each vertebral fracture adds roughly 4° to forward spine curvature. Sex steroids, in particular low bioavailable estradiol and high sex hormone–binding globulin (SHBG), are associated with bone loss and high SHBG is associated with vertebral fractures in older men. We, therefore, hypothesized that low bioavailable estradiol and high SHBG would be associated with worse kyphosis. To test this hypothesis, we examined the cross‐sectional associations between individual bioavailable sex hormones and SHBG with radiographically assessed kyphosis. Participants included 1500 men aged 65 and older from the Osteoporotic Fractures in Men (MrOS) Study, in whom baseline measures of kyphosis and sex hormones were available. Modified Cobb angle of kyphosis, calculated from T4 through T12, was assessed from supine lateral spine radiographs. Serum total estradiol and total testosterone were measured by mass spectrometry, and bioavailable sex steroids were calculated from mass action equations. After adjustment for age and other confounding variables, no association was found between bioavailable estradiol or testosterone and Cobb angle, either when kyphosis was analyzed as a continuous variable or dichotomized into highest versus lower three quartiles. In linear regression models adjusted for age and clinic site, there was a significant association between SHBG and kyphosis (parameter estimate = 0.76 per SD increase, p = 0.01). In the fully adjusted model, this association was weakened and of only borderline statistical significance (parameter estimate = 0.61 per SD, p = 0.05). Logistic models demonstrated similar findings. Although associated with bone loss, we did not demonstrate that low bioavailable estradiol translates into worse kyphosis in older men. High SHBG is associated with bone loss and vertebral fractures. Our results suggest that high SHBG may also be a risk factor for hyperkyphosis. © 2016 American Society for Bone and Mineral Research.